2010
DOI: 10.1021/tx100273g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Speciation of Trivalent Actinides and Lanthanides in Biological Fluids: The Dominant in Vitro Binding Form of Curium(III) and Europium(III) in Human Urine

Abstract: Radionuclides represent a serious health risk to humans in the case of incorporation. To elucidate the potential of time-resolved laser-induced fluorescence spectroscopy (TRLFS) to determine the dominant radionuclide species in natural biofluids, we investigated the in vitro speciation of curium(III) in human urine samples. Because in speciation studies trivalent lanthanides are often used as analogues for trivalent actinides, we also probed the suitability of this theory by investigating the speciation of eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
0
29
0
2
Order By: Relevance
“…In addition, citrate is a low molecular weight biological ligand that may play a predominant role in lanthanide in vivo 10 speciation. 31 However, the stabilities of citrate-lanthanide complexes (pM ranging from 8.3 for La III to 9.0 for Yb III ) 16 are substantially lower than those determined with 3,4,3-LI(1,2-HOPO). The octadentate hydroxypyridonate chelator can therefore form some of the strongest complexes so far identified with the trivalent metal ions of the lanthanide series, which makes it an excellent candidate for decorporation applications.…”
Section: Stability Increase Along the Lanthanide Seriesmentioning
confidence: 93%
“…In addition, citrate is a low molecular weight biological ligand that may play a predominant role in lanthanide in vivo 10 speciation. 31 However, the stabilities of citrate-lanthanide complexes (pM ranging from 8.3 for La III to 9.0 for Yb III ) 16 are substantially lower than those determined with 3,4,3-LI(1,2-HOPO). The octadentate hydroxypyridonate chelator can therefore form some of the strongest complexes so far identified with the trivalent metal ions of the lanthanide series, which makes it an excellent candidate for decorporation applications.…”
Section: Stability Increase Along the Lanthanide Seriesmentioning
confidence: 93%
“…In the presence of inorganic ions, the lanthanide ions are highly complexed and soluble (e.g., with chloride, sulfate, carbonate) as well as insoluble species (especially with phosphate) are formed. But also organic ligands (e.g., citrate) can complex lanthanides to a great extent, like was demonstrated for Eu(III) in human urine samples (Heller et al, 2011). The interactions of lanthanides with mammalian cells are only little studied up to now.…”
Section: Introductionmentioning
confidence: 98%
“…The experiments were performed as a function of the metal ion concentration and nutrient composition in order to correlate the behavior of the cells to the aqueous metal ion speciation. Besides the influence of fetal bovine serum (FBS) on the Eu(III) cytotoxicity and uptake, also that of citrate was studied because of its physiological relevance in all body fluids, especially in blood and urine (Boothby and Adams, 1934;Heller et al, 2011Heller et al, , 2012. The Eu(III) speciation in the nutrient media was investigated by thermodynamic modeling, solubility studies, ultrafiltration, ultracentrifugation, and time-resolved laser-induced fluorescence spectroscopy (TRLFS).…”
Section: Introductionmentioning
confidence: 99%
“…It is a reactive radionuclide which is used as component in fluorescent lamps, lasers, ceramics and catalysts for oil and nuclear industries. Radionuclides represent a serious health risk to humans in the case of incorporation [3]. Europium toxicity results in a significant decrease of creatinine and a significant increase of urinary volume, N-acetyl-b-D-glucosaminidase, and b-2-microglobulin.…”
Section: Introductionmentioning
confidence: 99%
“…Schott et al [34] and Horvath et al [35] reported that the cloud point of an aqueous solution containing a nonionic surfactant could be lowered by the addition of a salt. This is because the water molecules surrounding the nonionic surfactant are more strongly oriented toward the salt anions (e.g., NO 3 There are a few reports on the cloud point extraction of Eu(III) using chelating agents such as 2-(3,5-dichloro-2-pyridylazo)-5-diethylaminophenol [38], 8-quinolinol [39], and calixarenes [40]. Ohashi used di(2-ethylhexyl)phosphoric acid (HDEHP) and Triton X-100 for the extraction of Eu(III) [41].…”
Section: Introductionmentioning
confidence: 99%